The Social Validity of Telepractice among Spanish-Speaking Caregivers of English Learners: An Examination of Moderators - Lisa Fitton; Kristina N. Bustamante; Carla Wood (International Journal of Telerehabilitation)
The purpose of the present paper was to examine the social validity of telepractice as a service delivery model for Spanish-speaking families of English learners. Quantitative survey methodology was employed to examine 79 caregivers’ opinions regarding telepractice and to obtain background information about participants’ home environments. Findings revealed that approximately 46% of the participant sample reported being interested in their children receiving services via telepractice. Caregivers reported limited familiarity with telepractice as an option, but were likely to express interest if their child had an identified speech or language disorder or if they were interested in increased access to Spanish language support for their children. In conclusion, although telepractice is not universally accepted among Spanish-speaking families, it appears to be a promising service delivery model. It is recommended that service providers offer thorough information and address common myths when considering telepractice as a service delivery model for families.